Usage, Pleasure, Price, and Feeling: A Study on Shopping Orientation and Consumer Outcome - Zhao, Shaoqiong; Chen, Pu; Zhu, Yan; Wei, Feng; Liu, Fangmei (Frontiers in Psychology, 2022)
Understanding the behavior of consumers and especially the purchase-related behavior has been a focus of research for the past decades. Thus, researchers and practitioners are curious to know how purchase patterns are different under different conditions such as product category, price, feeling, and so on. The primary focus of this study was to examine how the price of the products influences the purchase behavior of consumers across hedonic and utilitarian categories under regulatory focus theory (RFT). The secondary insight was to examine how mood can moderate this impact. We conducted three experimental studies to examine these research questions regarding the preference of consumers of hedonic (utilitarian) products when the price is low (high) and at different mood conditions in this purchase process. The results confirmed our hypothesis that product category has a significant impact on purchase choice of products and mood can mediate this impact. In the last section, we discussed the theoretical contribution, strategic insights for product designers and marketers, and possible future research directions.